Semifluxons in long Josephson junctions with phase shifts - Ahmad, Saeed (2012)
A Josephson junction is formed by sandwiching a non-superconducting material between two superconductors. If the phase difference across the superconductors is zero, the junction is called a conventional junction, otherwise it is unconventional junction. Unconventional Josephson junctions are widely used in information process and storage. First we investigate long Josephson junctions having two p-discontinuity points characterized by a shift of p in phase, that is, a 0-p-0 long Josephson junction, on both infinite and finite domains. The system is described by a modified sine-Gordon equation with an additional shift q(x) in the nonlinearity. Using a perturbation technique, we investigate an instability region where semifluxons are spontaneously generated. We study the dependence of semifluxons on the facet length, and the applied bias current. We then consider a disk-shaped two-dimensional Josephson junction with concentric regions of 0- and p-phase shifts and investigate the ground state of the system both in finite and infinite domain. This system is described by a (2 + 1)